Electrochemical Impedance Spectroscopy and Adsorption Study of Carbon Steel in 1 M HCl Solution Containing 2-(2-Methoxybenzylidene) Hydrazine-1-Carbothioamide - Ferkous, Hana; Djellali, Souad; Sahraoui, Rachid; Behloul, Hamza; Saoud, Khaoula; Cukurovali, Alaaddin (Springer International Publishing Ag, 2021)
In this study, the ability of 2-(2-methoxybenzylidene) hydrazine-1-carbothioamide to inhibit carbon steel corrosion in hydrochloric acid (1 M) was investigated by means of electrochemical impedance spectroscopy. The adsorption parameters of the inhibitor on the metal surface were studied using three isotherm models: Langmuir, Temkin, and Frumkin. The results show that the compound under study exhibits inhibitor properties and may reach an inhibition efficiency of 97.9% at 200 ppm. The adsorption of this compound was found to corroborate with the Langmuir adsorption isotherm, and the obtained value of the free energy (Delta G degrees ads) suggests a predominant chemisorption of the used Schiff base on the steel surface.
2nd Euro-Mediterranean Conference for Environmental Integration-EMCEI -- OCT 10-13, 2019 -- Sousse, TUNISIA
Keywords: Schiff base; Corrosion inhibitor; Impedance spectroscopy; Adsorption; Isotherms